The efficiency characteristics analysis and optimization of the magnetic resonance wireless power transmission to multiple receivers. Issue 2 (7th March 2016) - Zhou, Jing; Gao, Yuqing; Huang, Xiaoyan; Fang, Youtong
Abstract : Purpose: – Consider the mutual coupling between loads, the purpose of this paper is to study the total transmission efficiency based on different load coil positions relative to the charging platform, to provide the theoretical basis for the design and parameter optimization of one-to-multiple wireless charging platform. Design/methodology/approach: – Based on the dual-load series-resonant wireless power transfer system, the expression of system efficiency and its calculation model is achieved using the equivalent circuit theory. Finally, a 96 kHz magnetic resonance wireless power transmission test platform is built up to verify the theoretical analysis given in this paper. Findings: – For the completely resonant circuit, the transmission efficiency can be improved by increasing the transmitter-receiver coupling and reducing the coupling between receivers. The total transmission efficiency achieves its lowest value when two loads are with equal competitive capability. Originality/value: – Through the simulation analysis of efficiency formula, the selection principle of impact factors can be applied to the optimization analysis of the transmission efficiency.